STRATEGIES FOR PREVENTION AND MECHANISMS FOR COUNTERING TAX EVASION IN AN INTERNATIONAL CONTEXT - Мединська Тетяна Володимирівна; Ruschyshyn Nadiia; Oliynyk Nadiya (Хмельницький національний університет (Україна), 2025)
This article is dedicated to the study of strategies and mechanisms for countering tax evasion in the international context, with a particular focus on the experiences of EU countries, the OECD, and Ukraine. The main elements of combating tax abuses, including legislative, administrative, and technological aspects, are examined. The paper analyzes key mechanisms for combating tax evasion used in EU and OECD countries. Special attention is paid to the BEPS (Base Erosion and Profit Shifting) initiative, which is a crucial tool for international cooperation in this area. The main elements of the "BEPS pillars" and their implementation tools are discussed, enabling the identification of the most effective approaches to countering tax abuses. An analysis of tax evasion combat methods in EU countries with developed tax systems is conducted. Key features and advantages of international experiences that can be utilized by Ukraine are identified. Particular attention is paid to the problems of tax evasion, which are especially relevant in the face of contemporary challenges and threats. The main challenges and opportunities for Ukraine in the context of international cooperation and the implementation of international standards are examined. The main elements of combating tax evasion in Ukraine are identified and analyzed. The article is based on an analysis of a wide range of literary sources, including data from international organizations, scholarly articles, legislative acts, and analytical reports. Comparative and systems analysis, as well as empirical research methods, are used.
СТРАТЕГІЇ ЗАПОБІГАННЯ ТА МЕХАНІЗМИ ПРОТИДІЇ УХИЛЕННЮ ВІД ОПОДАТКУВАННЯ У МІЖНАРОДНОМУ КОНТЕКСТІ
Modeling the development of the economic systems. № 1, 2025. P. 288-294
Keywords: tax evasion; tax abuses; international taxation; BEPS; European Union; tax administration; automatic exchange of information